Public policy as a nudger of cultural sustainability amidst rapid urbanization: A case of Delhi NCR - Bajpai, Vibhoo (The Scientific Temper, 2025)
As of 2025, more than 57% of the global population lives in urban areas, and this number is expected to rise to around 68% by 2050, according to the United Nations. India's urban population has experienced substantial growth, rising from 62 million in 1951 to 285 million in 2001 (Mohan& Dasgupta). Projections indicate that India will add 416 million urban dwellers by 2050, marking the largest urban population increase globally (United Nations,2018). These urban areas face challenges like climate change, pollution, and resource scarcity. The Central National Capital Region (CNCR) periphery experienced a significant increase in urban population, from 47% in 1991 to 69% in 2011. Urbanization is an inevitable consequence of economic growth and modernization, but its rapid pace often threatens intangible cultural heritage. This city sprawl has led to the displacement of traditional communities, loss of vernacular architecture, and erosion of local festivals leading to deteriorated condition of cultural heritage. This condition has posed a pressing challenge for the authorities and stakeholders. This research paper examines the existing government policy initiatives, focusing on the Delhi NCR, and analysing their implementation, outcomes, and challenges. This paper attempts to investigate the impact of urbanization on culture and the role of public policy in mitigating the challenges posed by rapid urban growth in facilitating cultural sustainability. The review draws upon the secondary data to provide a comprehensive understanding of the policy landscape, key issues, and potential areas for further research and action. The findings highlight the success and shortcomings of these policies and offer recommendations emphasizing the need for community-based approaches, cultural mapping, and inclusive urban policies to ensure that cultural heritage thrives amidst urban expansion.